2016
DOI: 10.1111/jnc.13559
|View full text |Cite
|
Sign up to set email alerts
|

Agonist‐induced activation of histamine H3 receptor signals to extracellular signal‐regulated kinases 1 and 2 through PKC‐, PLD‐, and EGFR‐dependent mechanisms

Abstract: The histamine H3 receptor (H3R), abundantly expressed in the central and the peripheral nervous system, has been recognized as a promising target for the treatment of various important CNS diseases including narcolepsy, Alzheimer's disease, and attention deficit hyperactivity disorder. The H3R acts via G i/o -proteins to inhibit adenylate cyclase activity and modulate MAPK activity. However, the underlying molecular mechanisms for H3R mediation of the activation of extracellular signal-regulated kinases 1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The EGFR family has received much attention in pharmacological research due to their strong association with malignant proliferation (Gallick et al, 2012). In addition to direct activation by specific ligands, EGFR family members could also be transactivated by a variety of GPCR agonists (Daub et al, 1996;Zhou et al, 2012;Cattaneo et al, 2014;Muñoz-Moreno et al, 2014;Lai et al, 2016;Wang, 2016). In this study, we demonstrated for the first time that specific activation of GABA B R, a neurotransmitter receptor belonging to the GPCR family, selectively induced EGFR transactivation in PC-3 cells.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The EGFR family has received much attention in pharmacological research due to their strong association with malignant proliferation (Gallick et al, 2012). In addition to direct activation by specific ligands, EGFR family members could also be transactivated by a variety of GPCR agonists (Daub et al, 1996;Zhou et al, 2012;Cattaneo et al, 2014;Muñoz-Moreno et al, 2014;Lai et al, 2016;Wang, 2016). In this study, we demonstrated for the first time that specific activation of GABA B R, a neurotransmitter receptor belonging to the GPCR family, selectively induced EGFR transactivation in PC-3 cells.…”
Section: Discussionmentioning
confidence: 70%
“…GPCR-induced EGFR transactivation can activate ERK1/2 signaling cascades (Xiao et al, 2003;Zhou et al, 2012;George et al, 2013;Lai et al, 2016). To examine whether EGFR transactivation by GABA B R induced ERK1/2 activation, PC-3 cells were treated with baclofen or GABA for various period of Fig.…”
Section: Gaba B R Agonist-induced Activation Of Erk1/2 In Human Pca Cmentioning
confidence: 99%
“…Our work and those of others have suggested that PKC, PKA, and Bcl-2 are directly or indirectly involved in MAPK signaling in hypoxic injury or protection against hypoxic injury. 27 , 66 69 For example, Bcl-2 confers protection against nuclear mitochondrial impairment under oxidative stress in pheochromocytoma (PC-12) cells, and a reduction in Bcl-2 expression leads to cell injury. 70 However, we did not find any appreciable change in the kidney epithelial cells, even after 72 h of hypoxia, which was different from what we saw in hypoxic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, FoxC2 siRNA suppressed β1-integrin expression and EP1R-mediated cell migration in NSCLC cells; the EP1 agonist improved FoxC2 expression; while Rottlerin suppressed EP1R-mediated FoxC2 expression significantly; ChIP assay identified that EP1 agonist treatment increased FoxC2 binding to β1-integrin promoter. MAPKs are involved in PKC downstream signalling pathway 32 33 . We found that the EP1 agonist improved both Erk1/2 and p38 phosphorylation in A549 cells, and that MEK1/2 and p38 inhibitors, suppressed EP1R-mediated β1-integrin upregulation.…”
Section: Discussionmentioning
confidence: 99%